FATHER’S ROLE IN PARENTING: A CASE STUDY FROM GAY STUDENT PERCEPTION - Wahyu Saefudin; Lisnawati Lisnawati; Sriwiyanti Sriwiyanti (Jurnal Psikologi Integratif, 2021)
Despite reaping the pros and cons of the community, the presence of gay students continues to increase. This study aims to see how the role of fathers in parenting and education from the perception of gay students. The method used is qualitative with a case study approach, with analysis using coding techniques. The subjects of this study were two students who claimed to be gay. Based on the results of the analysis of the two participants, it shows that fathers have a minor role in parenting and education. The father's role is decreased because the work location is far away. The interaction of the participants becomes dominant with the mother and older sister. The mother figure becomes the only role model who sets an example, disciplines, controls, and monitors. The dominance of the mother's role made both participants more comfortable communicating with the mother than the father. The lack of father involvement in parenting and education makes the chosen activities, role models, and role replication depend on the mother figure and older sister. The condition of the lack of paternal care and the dominant role of the mother strengthen the risk of gender identity perplexing that occurs in gay students.Keywords: Gay Student, Parenting, Fatherless, Gender IdentityMeskipun menuai pro dan kontra dari masyarakat, keberadaan mahasiswa gay terus meningkat. Penelitian ini bertujuan untuk melihat bagaimana peran ayah dalam pengasuhan dan pendidikan dari persepsi mahasiswa gay. Metode yang digunakan adalah metode penelitian kualitatif dengan pendekatan studi kasus, dengan analisis menggunakan teknik koding. Subjek penelitian ini adalah dua orang mahasiswa yang mengaku sebagai gay. Berdasarkan hasil analisis kedua partisipan, menunjukkan bahwa ayah mempunyai peran yang kurang dalam pengasuhan dan pendidikan. Peran ayah menjadi berkurang karena lokasi kerja yang jauh, sehingga interaksi partisipan menjadi dominan dengan ibu dan kakak perempuan. Figur ibu menjadi satu-satunya role model yang memberi contoh, mendisiplinkan, mengontrol, dan memantau. Dominasi peran ibu membuat kedua partisipan lebih nyaman untuk berkomunikasi dengan ibu dibandingkan ayah. Kurangnya keterlibatan ayah dalam pengasuhan dan pendidikan menjadikan aktivitas yang dipilih, teladan, hingga replikasi peran bergantung pada sosok ibu serta kakak perempuan. Kondisi kurangnya pengasuhan ayah dan dominannya peran ibu memperkuat risiko kebingungan identitas gender yang terjadi pada mahasiswa gay.Kata kunci: Mahasiswa Gay, Pengasuhan, Peran Ayah, Identitas Gender